Method for producing high-purity metal cobalt from waste hydrogenation catalyst

Through the steps of roasting, water leaching, acid dissolution leaching, extraction, vanadium removal and electrodisposition, nickel, cobalt and vanadium in the waste hydrogenation catalyst were successfully separated and recovered, solving the difficulty of deep separation between cobalt and vanadium, and achieving high purity and high-quality metal cobalt production.

CN119553094AActive Publication Date: 2025-03-04广西银亿新材料有限公司 +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411737866.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-04
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

The prior art is difficult to effectively utilize cobalt in the waste hydrogenation catalyst, and the depth separation between cobalt and vanadium is difficult, affecting the purity and quality of metal cobalt.

Method used

Through the steps of calcining, water leaching, acid dissolution leaching, extraction, vanadium removal and electrodisposition, nickel, cobalt and vanadium in the waste hydrogenation catalyst are separated and recovered, and the deep adsorption of vanadium is used to use D402 resin, and high-purity metal cobalt is produced by electrodistribution.

Benefits of technology

The efficient separation of nickel, cobalt and vanadium was achieved, and high-purity (99.95% or more) and high-quality metal cobalt was obtained. The current efficiency of the electrodistribution process reached more than 85%, and the cobalt plate layering phenomenon was avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119553094A_ABST
    Figure CN119553094A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of extraction of metal cobalt from waste materials, and particularly relates to a method for producing high-purity metal cobalt from a waste hydrogenation catalyst, which comprises the following steps: (1) roasting and water leaching; (2) acid dissolution and leaching; (3) extracting; (4) removing vanadium; and (5) carrying out cobalt electrodeposition to obtain high-purity metal cobalt. By adopting the method disclosed by the invention, high-purity and high-quality metal cobalt can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of extracting metallic cobalt from waste materials, and in particular relates to a method for producing high-purity metallic cobalt from waste hydrogenation catalysts. Background Art

[0002] Catalysts generally refer to substances that can increase the rate of chemical reactions without changing the chemical equilibrium, and whose quality and chemical properties do not change before and after the chemical reaction. Hydrogenation catalysts are one of the most important catalysts in the oil refining process. They are used to catalyze hydrogenation desulfurization, denitrogenation, deoxidation, demetallization, etc., to improve the quality and yield of finished oil. Hydrogenation catalysts usually use Al2O3 as carriers, and valuable metals such as nickel and cobalt or their oxides as active components are evenly dispersed on the surface and pores of the carrier. They are widely used in oil refining and chemical industries. After a certain period of use, they will gradually lose their activity due to carbon deposition, metal deposition and other reasons, forming a large amount of hazardous solid waste containing oily substances and heavy metals. During the hydrogenation process, the vanadium metal component in the residual oil will gradually deposit on the catalyst surface. Therefore, the waste hydrogenation catalyst usually contains valuable metals such as oil, vanadium, nickel, cobalt and alumina carriers. The valuable metals such as vanadium, nickel and cobalt have high recovery value. Considering resource utilization and environmental protection, it is necessary to recycle them.

[0003] Metallic cobalt can be used as an important raw material for positive electrode materials of lithium-ion batteries in the field of new energy vehicles. It is also widely used in the field of electronic chemical industry and the preparation of special alloys. It is an important material for the preparation of magnetic recording, magnetic recording heads, optoelectronic devices, magnetic sensors, integrated circuits and other components. Cobalt with a purity of 99.9% to 99.99% has been widely used in the manufacture of magnetic materials and super alloys, and cobalt with a purity of 99.999% or even higher is used as a target material for advanced electronic components.

[0004] Valuable metal elements in waste hydrogenation catalysts exist in various forms such as oxides, sulfides, salts, and multi-metallic complexes, and separation and recovery are extremely difficult. CN118308607A discloses a method for recovering vanadium in waste hydrogenation catalysts, the method comprising: evenly mixing waste hydrogenation catalysts with sodium carbonate and sodium aluminate solutions, and then roasting to obtain roasted clinker, leaching the roasted clinker in an alkaline solution to obtain leached slag rich in nickel and cobalt and sodium aluminate solution rich in vanadium, then adding calcium-containing compounds to remove impurities to obtain a vanadium-rich solution, and finally adding barium-containing compounds to the vanadium-rich filtrate to obtain a vanadium-containing precipitate for recovery. However, the cobalt in the waste catalyst is not effectively utilized. It can be concluded from multiple embodiments of CN113293297A and other prior arts that the vanadium recovery rate can only reach 70-98%, and there is still 2-30% of vanadium left in the leaching residue rich in nickel and cobalt. It can be predicted that when the conventional process is used to recover nickel and cobalt from the leaching residue rich in nickel and cobalt, this part of vanadium will be leached, extracted, and stripped together with the nickel and cobalt. When it is used to produce high-purity metallic cobalt, the presence of vanadium will also affect the purity of the metallic cobalt. When high-purity metallic cobalt is produced by electrowinning, low concentrations of vanadium will have an impact on the electrowinning process, specifically including: vanadium exists in a variety of valence states in aqueous solution, and its existence form is easy to change, resulting in a very easy reduction in current efficiency during electrowinning. When vanadium and cobalt coexist, the electrowinning behavior of vanadium will lead to uneven cobalt metal deposition and cobalt plate stratification, and will also lead to a reduction in the purity of metallic cobalt. Therefore, when using waste hydrogenation catalysts to recover and prepare high-purity metallic cobalt, the deep separation of cobalt and vanadium is very critical. The separation of cobalt and vanadium in the cathode liquid of electrowinning will directly affect the purity and quality of metallic cobalt. Summary of the invention

[0005] The present invention aims to solve the above technical problems and provides a method for producing high-purity metallic cobalt from waste hydrogenation catalysts, which can prepare high-purity and high-quality metallic cobalt.

[0006] The technical solution of the present invention is:

[0007] A method for producing high-purity metallic cobalt from spent hydrogenation catalyst comprises the following steps:

[0008] (1) Calcination and water leaching: the spent hydrogenation catalyst is calcined with sodium carbonate and sodium hydroxide under aerobic conditions, cooled naturally, leached with water, and solid-liquid separated to obtain a vanadium-containing leaching solution and water-leached residue;

[0009] (2) Acid leaching: Acid leaching is performed on the water leaching residue to extract nickel and cobalt. After the leaching is completed, the solid and liquid are separated to obtain a nickel-cobalt solution and acid leaching residue;

[0010] (3) Extraction: the nickel-cobalt solution is mixed with P204 to extract impurities, the P204 raffinate is mixed with extractant A to extract cobalt, and the raffinate A and loaded organic phase A are obtained; the loaded organic phase A is mixed with an inorganic acid solution to strip cobalt, and the vanadium removal pre-liquid and the stripped organic phase A are obtained;

[0011] (4) Vanadium removal: adjusting the pH of the pre-vanadium removal solution to 0-1.5, and then passing it through the pretreated D402 resin to dynamically adsorb vanadium to obtain a post-vanadium removal solution;

[0012] (5) Cobalt electrowinning: Adjust the pH of the solution after vanadium removal to 1.5-4.0, add boric acid to obtain a cathode solution, and electrowinning the cathode solution to obtain high-purity metallic cobalt.

[0013] Preferably, in step (1) of the present invention, the amount of sodium hydroxide used is 1.2-1.5 times the theoretical amount used for the reaction with vanadium and alumina (calculated according to the reaction of V2O5+6NaOH=2Na3VO4+3H2O, Al2O3+2NaOH=2NaAlO2+H2O), and the amount of sodium carbonate used is 30-60% of the weight of sodium hydroxide. When the amount of sodium hydroxide used is too little, the vanadium conversion is incomplete, and a large amount of vanadium remains in the water leaching residue after water leaching, so the dissolution of vanadium increases during the subsequent acid leaching, and the material is easy to agglomerate after roasting. When the amount of sodium hydroxide used is too much, on the one hand, the consumption of sodium hydroxide is increased, and the material is easy to agglomerate after roasting. On the other hand, the alkali residue in the subsequent vanadium-containing leachate is high, which increases the recovery cost. When the amount of sodium carbonate used is too little, the material is easy to agglomerate after oxidation roasting, which is not conducive to the subsequent material transfer and water leaching. When the amount of sodium carbonate used is too much, on the one hand, the consumption of sodium carbonate is increased, and on the other hand, the alkali residue in the nickel-cobalt solution obtained by subsequent water leaching is high, which increases the recovery cost.

[0014] Preferably, in step (1) of the present invention, the roasting method is staged roasting: the first stage roasting temperature is 300-400°C, the time is 1-3h, and the main purpose of the first stage roasting is to remove the oil and oxidative decomposition of organic matter in the waste catalyst; the second stage roasting temperature is 600-1000°C, the time is 1-3h, and the second stage roasting mainly produces the conversion reaction of vanadium and aluminum oxide. The main forms of vanadium in the waste hydrogenation catalyst are vanadium trioxide, vanadium pentoxide, and vanadium sulfide, nickel and cobalt mainly exist in the form of nickel sulfide, cobalt sulfide, etc., and aluminum exists in the form of aluminum oxide. During roasting, the role of the added sodium hydroxide is mainly to generate sodium metavanadate, sodium vanadate, and sodium metaaluminate solids that are easily soluble in water through its reaction with vanadium oxide and aluminum oxide. Therefore, vanadium, aluminum and other valuable metals can be separated by water leaching and solid-liquid separation, and other valuable metals are left in the water leaching residue and can be further recovered. Adding sodium carbonate during roasting can prevent the material from agglomerating after roasting and extend the service life of the equipment. Adding sodium hydroxide and waste hydrogenation catalyst alone for oxidation roasting is easy to agglomerate, which is not conducive to the subsequent transfer and water immersion of materials. During water immersion, sodium vanadate can react with water to form sodium metavanadate, which is easily soluble in water.

[0015] Preferably, in step (1) of the present invention, water is added to a solid content of 20-35 wt.%, the water immersion temperature is 60-95° C., the time is 1-4 h, and the water immersion after roasting is carried out. Heating is beneficial to accelerate the dissolution reaction of the vanadium compound.

[0016] Preferably, in step (2) of the present invention, the pH value of the acid dissolution process is controlled to be 0.5-1.5, so that the nickel and cobalt in the water leaching residue can be fully leached. When the pH value is too high, the nickel and cobalt can not be completely leached. When the pH value is too low, the amount of inorganic acid used is too large. Heating is conducive to accelerating the acid dissolution and leaching reaction. The acid dissolution time is 1-4h and the temperature is 60-95°C. The nickel and cobalt leaching rate during acid dissolution is more than 99%, and the vanadium distribution in the acid leaching residue is 1-8%. The inorganic acid during acid dissolution of the present invention is preferably sulfuric acid or hydrochloric acid.

[0017] Preferably, in step (3) of the present invention, the phase ratio of P204 is controlled at 1-2:1 when mixed to extract impurities, the extractant A is P507 or Cyanex272, and the phase ratio of cobalt is controlled at 1-1.5:1 when extracting cobalt.

[0018] The spent hydrogenation catalyst contains valuable metals such as nickel, cobalt, vanadium and a small amount of other impurities. The nickel-cobalt solution obtained after oxidation roasting-water leaching and acid leaching contains nickel, cobalt, a small amount of vanadium, and a small amount of calcium, iron, aluminum, etc., which can be separated by extraction with P204 and extractant A. In this process, vanadium is successively extracted by P204 and extractant A in small amounts. In order to recover the cobalt, extractant A needs to be stripped of cobalt with inorganic acid. However, while stripping cobalt, the vanadium loaded by extractant A will also be stripped with cobalt and enter the vanadium removal pre-liquid. Therefore, in order to produce high-purity metallic cobalt, the vanadium needs to be deeply removed. In the field of nickel-cobalt metallurgy, P507 and Cyanex272 are commonly used to separate nickel and cobalt from solutions containing nickel and cobalt. Therefore, the extractant A of the present invention is preferably P507 or Cyanex272. By controlling the extraction conditions, cobalt can be extracted while only a small amount of nickel or no nickel is extracted. Nickel is then recovered from the raffinate, and the organic phase loaded with cobalt is stripped with an inorganic acid to obtain a cobalt sulfate or cobalt chloride solution, and finally cobalt is further recovered. The loaded organic phase A can be stripped of cobalt by inorganic acid, the concentration of the inorganic acid is preferably 2-4N, and the inorganic acid is preferably sulfuric acid and hydrochloric acid. When stripping cobalt, the cobalt concentration needs to be controlled at 80-110g / L, and the pH of the outlet aqueous phase is controlled to be 2.0-2.5. Before stripping cobalt, the loaded organic phase A needs to be washed with nickel to ensure the complete separation of nickel and cobalt, to prevent a small amount of loaded nickel from entering the vanadium removal pre-liquid with the cobalt, and to increase the burden of subsequent nickel removal. When washing nickel, an inorganic acid is used, preferably with an inorganic acid concentration of 0.5-1.5N, and the pH of the outlet aqueous phase is controlled to be 3.0-4.0 to prevent the cobalt from being washed together and reduce the cobalt recovery rate.

[0019] D402 resin is a macroporous styrene-based aminophosphonic acid chelating ion exchange resin, which is mainly used for the adsorption of calcium, magnesium, copper ions, etc. in wastewater treatment to reduce the hardness of wastewater. It can also adsorb a small amount of nickel, cobalt, and other heavy metal ions, and is used for the treatment of wastewater containing low concentrations of nickel, cobalt, and heavy metals. The above adsorption processes are all carried out under neutral or alkaline conditions. The inventors of the present invention have found through multiple experimental verifications that D402 resin can also be used for the adsorption of vanadium under acidic conditions, and the coexisting calcium, magnesium, copper, nickel, and cobalt ions are not adsorbed at this time. Therefore, it can be used for the deep separation of cobalt and vanadium in the present invention, and the vanadium-removed liquid can be further used to produce high-purity metallic cobalt. When pH <2, +5 valence vanadium is mainly in the form of VO2 + The +4 vanadium exists in the form of VO 2+ There are two forms of vanadium. When the pH is higher than 2, +5 valence vanadium exists in various forms. When the acidity is lower, +4 valence vanadium also exists in various forms. D402 resin can adsorb the above two forms of vanadium, so it can be used for the deep separation of cobalt and vanadium under acidic conditions of the present invention.

[0020] Preferably, in step (4) of the present invention, in order to convert the D402 resin to a hydrogenated form, the pretreatment of the D402 resin is specifically as follows: a 5-10% inorganic acid solution, preferably hydrochloric acid or sulfuric acid, is used for dynamic washing at a flow rate of 3-5BV / h, and then the residual acid is washed with pure water at a flow rate of 3-5BV / h. The washing is stopped when the pH at the washing water outlet is 3-4, and the pretreatment is completed.

[0021] When the temperature is too low or the flow rate of the pre-vanadium removal liquid is too fast when D402 resin adsorbs vanadium, the pre-vanadium removal liquid stays in the resin layer for a short time and the contact between the two is insufficient, which will lead to a slow adsorption rate and poor adsorption effect. When the temperature is too high, it is not conducive to operation and the energy consumption is high. When the flow rate of the pre-vanadium removal liquid is too slow, the production efficiency is low. Therefore, in step (4) of the present invention, when D402 resin adsorbs vanadium, the adsorption temperature is preferably controlled at 20-40°C, and the flow rate of the pre-vanadium removal liquid is preferably 2-5BV / h.

[0022] Preferably, in step (5) of the present invention, the control conditions for electrolytic cobalt deposition are: electrolytic cell temperature 55-65°C, current density 180-220A / m 2, isopole moment 10-15cm. Increasing the temperature can promote the diffusion of cobalt ions, reduce concentration polarization, reduce the cell voltage, and improve the current efficiency. At the same time, increasing the temperature can accelerate the growth rate of cathode deposit grains and make the cathode cobalt crystal particles larger. However, if the temperature is too high, it will increase energy consumption, reduce the superpotential of hydrogen, and then increase hydrogen precipitation and reduce the current efficiency. When the temperature is too low, it will lead to phenomena such as cathode stratification. The practice of electrolytic cobalt shows that controlling the temperature of the electrolyte at 55-65°C can take into account higher current efficiency, smooth surface of metal cobalt and purity of metal cobalt. The greater the current density, the greater the output. However, as the current density increases, the cell voltage increases and the current efficiency decreases. At the same time, the cathode cobalt surface obtained under high current density is rough and easy to adsorb impurity particles. Therefore, the current density of the present invention is preferably 180-220A / m 2 Using the smallest possible inter-electrode distance is not only beneficial to reducing the cell voltage and improving the current efficiency, but also increasing the production capacity of the electrolytic cell. However, if the inter-electrode distance is too small, it is easy to increase the contact in the cell and cause short circuit, which brings many difficulties to the operation and management of the cell surface and reduces the current efficiency. Therefore, the inter-electrode distance of the present invention is preferably 10-15cm.

[0023] The titanium-plated iridium-tantalum plate has good electrical conductivity and good corrosion resistance, and can prevent the anode corrosive products from entering the cathode metal cobalt. There is no need to add a diaphragm for electrowinning. When the cobalt starting plate is used as the cathode in the present invention, there is no need to peel the cobalt plate, thereby reducing the labor intensity. Therefore, the present invention preferably uses the cobalt starting plate as the cathode, the titanium-plated iridium-tantalum plate as the anode, and the diaphragm-free electrowinning of cobalt.

[0024] When electrolytically depositing cobalt, the invention adds a certain amount of boric acid to improve the quality of metallic cobalt. During the electrolytic deposition process, the precipitation of cathode hydrogen is inevitable, and the pH value of the electrolyte on the cathode surface rises, which easily leads to the hydrolysis of cobalt ions to form basic salt precipitation adsorbed on the cathode surface and affects the product quality. When boric acid is added to the electrolyte, since it is a weak acid, there is an ionization equilibrium in the solution. If the pH value of the solution rises, H + , in order to maintain the stability of the pH value of the electrolyte. The practice of electrolytic cobalt production shows that when the boric acid concentration is too high, the cathode current efficiency will be reduced, and it is easy to crystallize at low temperatures, resulting in rough surface and burrs of the electrolytic cobalt plate and waste of raw materials. Therefore, the present invention preferably adds boric acid at a concentration of 6-15g / L.

[0025] When electrowinning cobalt, the greater the acidity of the cathode liquid (the lower the pH), the more hydrogen ions are precipitated at the cathode during the electrowinning process, and the lower the current efficiency. When the pH value of the cathode liquid is high, cobalt hydroxide is easily generated on the cathode, and the produced cathode cobalt has high hardness, poor elasticity, and is easy to stratify. The preferred cathode liquid pH of the present invention is 1.5-4.0.

[0026] In order to reuse the resin, the method of the present invention also includes step (6): desorbing and regenerating the vanadium-loaded resin, using ammonia water with a mass concentration of 2-5% or liquid alkali with a mass concentration of 2-5% during desorption, the temperature during desorption is 20-40°C, and the desorbent flow rate is 1-3BV / h; during regeneration, using an inorganic acid solution with a mass concentration of 5-10%, preferably hydrochloric acid or sulfuric acid, the temperature is 20-40°C, and the inorganic acid solution flow rate is 3-5BV / h. Before desorption and regeneration, the resin is first washed with pure water, and the regenerated D402 resin can be returned to step (4) for use.

[0027] Due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0028] 1. The method of the present invention can realize the separation of nickel, cobalt and vanadium. By deeply adsorbing vanadium with D402 and then performing electrowinning, high-purity metallic cobalt can be obtained, and its purity can reach more than 99.95%. The current efficiency in the electrowinning process can reach more than 85%.

[0029] 2. The method of the present invention not only obtains high-purity metallic cobalt, but also has high quality, that is, the surface of the electrolytic cobalt obtained is flat, the electrolytic deposition time is 5 days, and no cobalt plate stratification occurs.

[0030] 3. The method of the present invention can solve the problem of easy agglomeration of the calcined material obtained by oxidative calcination of the waste hydrogenation catalyst with sodium hydroxide in the traditional method. The calcination-water leaching process can separate vanadium and nickel and cobalt in the waste hydrogenation catalyst, laying a good foundation for the subsequent high-purity extraction of metallic cobalt. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 The present invention is a flow chart of the method for producing high-purity metallic cobalt from spent hydrogenation catalyst. DETAILED DESCRIPTION

[0032] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] Example 1

[0034] A method for producing high-purity metallic cobalt from spent hydrogenation catalyst comprises the following steps:

[0035] (1) Calcination-water leaching: The spent hydrogenation catalyst (nickel 36.5%, cobalt 14.4%, vanadium 2.42%) was calcined with sodium carbonate and sodium hydroxide under aerobic conditions. The calcination conditions were as follows: the amount of sodium hydroxide was 1.5 times the theoretical amount of sodium hydroxide used for its reaction with vanadium and alumina (calculated according to the reaction of V2O5+6NaOH=2Na3VO4+3H2O, Al2O3+2NaOH=2NaAlO2+H2O), and the amount of sodium carbonate was 30wt% of the amount of sodium hydroxide used; the calcination method was staged calcination: one-stage calcination During the second stage calcination, the material was kept at 300°C for 3 hours. During the second stage calcination, the material was kept at 800°C for 2 hours. After the calcination, the material was naturally cooled. There was no obvious agglomeration phenomenon in the calcined material. The calcined material was leached with water at a solid content concentration of 20wt.%, the leaching temperature was 60°C, the time was 4h, and the solid-liquid separation was performed to obtain a vanadium-containing leaching solution and a leaching residue. The distribution of nickel and cobalt in the vanadium-containing leaching solution was less than 0.1%, the distribution of vanadium was 97.88%, and the distribution of vanadium in the leaching residue was 2.12%. The calcination-water leaching process preliminarily achieved the separation of vanadium and nickel and cobalt in the spent hydrogenation catalyst.

[0036] (2) Acid leaching: the water leaching residue is slurried with water according to a liquid-solid mass ratio of 3:1 ml / g, and a hydrochloric acid solution with a mass concentration of 20% is added for acid dissolution. The pH value of the acid dissolution process is controlled to be 1.2, the acid dissolution time is 3 hours, and the temperature is 80°C. The solid-liquid separation is performed to obtain a nickel-cobalt solution and an acid leaching residue. During the acid dissolution, the nickel-cobalt leaching rate is more than 99%, and the vanadium leaching rate in the acid leaching residue is 75.12% (based on the raw material waste hydrogenation catalyst, the vanadium distribution in the vanadium-containing leaching solution is 97.88%, the vanadium distribution in the acid leaching residue is 0.53%, and the vanadium distribution in the nickel-cobalt solution is 1.59%).

[0037] (3) Extraction: Mix the nickel-cobalt solution with P204 to extract impurities, and mix the P204 raffinate with P507 to extract cobalt, to obtain a raffinate A and a loaded organic phase A; add 1N hydrochloric acid solution to the loaded organic phase A to wash nickel, control the pH of the washing solution to 3.0, to obtain a nickel-containing washing solution and an organic phase A after nickel washing; mix the organic phase A after nickel washing with 2N hydrochloric acid solution to strip cobalt, control the pH of the stripping solution to 2.2, and the cobalt concentration of the stripping solution to 80 g / L, to obtain a vanadium removal pre-liquid and an organic phase A after stripping;

[0038] P204 mixed extraction impurity conditions: P204 volume concentration 25%, before extraction, P204 sodium saponification with liquid alkali, saponification rate 50%, after sodium soaping, nickel sulfate solution (nickel concentration 30g / L) nickel soaping, saponification temperature 40℃, time 5min, phase ratio 1:1.5, so as to remove the sodium ions introduced by sodium soap, impurity extraction temperature 40℃, single-stage extraction time 5min, phase ratio 1.5:1, extraction method is countercurrent extraction 4 stages;

[0039] The conditions for the mixed extraction of cobalt with P507 are as follows: the volume concentration of P507 is 15%. Before extraction, sodium P507 is saponified with liquid alkali, with a saponification rate of 60%. The temperature during saponification is controlled at 40°C, the time is 5 minutes, and the phase ratio is 1.5:1. When extracting cobalt, the temperature is controlled at 40°C, the single-stage extraction time is 5 minutes, the phase ratio is 1.5:1, and the extraction method is 4-stage countercurrent extraction.

[0040] (4) Vanadium removal: hydrochloric acid was added to the pre-vanadium removal solution (vanadium concentration 0.13 g / L) to adjust the pH to 1.0, and then the solution was passed through the pretreated D402 resin for dynamic adsorption of vanadium to obtain a post-vanadium removal solution (vanadium concentration 0.1 mg / L). The adsorption temperature was 20°C and the flow rate of the pre-vanadium removal solution was 2 BV / h.

[0041] D402 resin pretreatment: Dynamically wash with 10% hydrochloric acid solution at a flow rate of 3BV / h, and then wash the residual acid with pure water at a flow rate of 3BV / h. Stop washing when the pH of the washing water outlet is 3.0, and the pretreatment process is completed;

[0042] (5) Cobalt electrowinning: Add caustic soda to the vanadium-removed solution to adjust the pH to 4.0, add boric acid to obtain a cathode solution, and electrowinning the cathode solution. When electrowinning cobalt, the cathode is a cobalt starting plate, the anode is a titanium-plated iridium-tantalum plate, and there is no diaphragm electrowinning. Boric acid is added at a dosage of 15 g / L. When electrowinning cobalt, the electrolytic cell temperature is controlled at 55°C and the current density is 180 A / m 2 , the same polar moment is 10cm, and high-purity metallic cobalt is obtained, with a purity of 99.98%. The current efficiency of the electrolytic process is 87.91%. The surface of the electrolytic cobalt obtained is flat, and the electrolytic time is 5 days, and no cobalt plate stratification occurs;

[0043] (6) Resin desorption and regeneration: First, wash the resin with pure water, then desorb and regenerate the vanadium-loaded resin. During desorption, use 5% ammonia water to flow through the vanadium-loaded resin, control the desorption temperature to 20°C, and the desorbent flow rate to 1BV / h. During regeneration, use 10% hydrochloric acid solution, and control the flow rate of the hydrochloric acid solution to 3BV / h. The regenerated D402 resin can be returned to step (4) for use.

[0044] Example 2

[0045] A method for producing high-purity metallic cobalt from spent hydrogenation catalyst comprises the following steps:

[0046] (1) Calcination-water leaching: The spent hydrogenation catalyst (nickel 33.5%, cobalt 20.83%, vanadium 5.42%) was calcined with sodium carbonate and sodium hydroxide under aerobic conditions. The calcination conditions were as follows: the amount of sodium hydroxide was 1.3 times the theoretical amount of sodium hydroxide used for reaction with vanadium and alumina, and the amount of sodium carbonate was 60 wt.% of the amount of sodium hydroxide used. The calcination method was staged calcination: in the first stage, the temperature was kept at 350°C for 2 hours, and in the second stage, the temperature was kept at 1000°C for 2 hours. The calcined material was kept warm for 1 hour at a temperature of 85°C after being naturally cooled after calcination. There was no obvious agglomeration phenomenon in the calcined material. The calcined material was leached with water at a solid content concentration of 35wt.%, the leaching temperature was 85°C, and the time was 3h. The solid-liquid separation was performed to obtain a vanadium-containing leaching solution and a leaching residue. The distribution of nickel and cobalt in the vanadium leaching solution was less than 0.1%, the distribution of vanadium was 95.67%, and the distribution of vanadium in the leaching residue was 4.33%. The calcination-water leaching process preliminarily achieved the separation of vanadium and nickel and cobalt in the spent hydrogenation catalyst.

[0047] (2) Acid leaching: the water leaching residue is slurried with water according to a liquid-solid mass ratio of 4:1 ml / g, and sulfuric acid with a mass concentration of 50% is added for acid dissolution. The pH value of the acid dissolution process is controlled to be 0.5, the acid dissolution time is 4 hours, and the temperature is 60°C. The solid-liquid separation is performed to obtain a nickel-cobalt solution and an acid leaching residue. During the acid dissolution, the nickel-cobalt leaching rate is more than 99%, and the vanadium leaching rate in the acid leaching residue is 66.83% (based on the raw material waste hydrogenation catalyst, the vanadium distribution in the vanadium-containing leaching solution is 95.67%, the vanadium distribution in the acid leaching residue is 1.44%, and the vanadium distribution in the nickel-cobalt solution is 2.89%).

[0048] (3) Extraction: Mix the nickel-cobalt solution with P204 to extract impurities, and mix the P204 raffinate with P507 to extract cobalt, to obtain a raffinate A and a loaded organic phase A; add a 0.5N sulfuric acid solution to the loaded organic phase A and wash the nickel, control the pH of the wash solution to 3.4, to obtain a nickel-containing wash solution and an organic phase A after nickel washing; mix the organic phase A after nickel washing with a 4N sulfuric acid solution to strip cobalt, control the pH of the stripping solution to 2.0, and the cobalt concentration of the stripping solution to 92 g / L, to obtain a vanadium removal pre-liquid and an organic phase A after stripping;

[0049] P204 mixed extraction impurity conditions: P204 volume concentration 18%, before extraction, P204 sodium saponification with liquid alkali, saponification rate 55%, after sodium soaping, nickel sulfate solution (nickel concentration 30g / L) nickel soaping, saponification temperature 30℃, time 10min, phase ratio 1:2, so as to remove the sodium ions introduced by sodium soap, impurity extraction temperature 30℃, single-stage extraction time 10min, phase ratio 2:1, extraction method is countercurrent extraction 4 levels;

[0050] The conditions for the mixed extraction of cobalt with P507 are as follows: the volume concentration of P507 is 20%. Before extraction, sodium P507 is saponified with liquid alkali, with a saponification rate of 55%. The temperature during saponification is controlled at 30°C, the time is 10 min, and the phase ratio is 1:1. When extracting cobalt, the temperature is controlled at 30°C, the single-stage extraction time is 10 min, the phase ratio is 1:1, and the extraction method is 4-stage countercurrent extraction.

[0051] (4) Vanadium removal: sulfuric acid was added to the pre-vanadium removal solution (vanadium concentration 0.58 g / L) to adjust the pH to 0, and then the solution was passed through the pretreated D402 resin for dynamic adsorption of vanadium to obtain a post-vanadium removal solution (vanadium concentration 0.3 mg / L). The adsorption temperature was 30°C and the flow rate of the pre-vanadium removal solution was 5 BV / h.

[0052] D402 resin pretreatment: Dynamically wash with 5% sulfuric acid solution at a flow rate of 5BV / h, and then wash the residual acid with pure water at a flow rate of 5BV / h. Stop washing when the pH of the washing water outlet is 4.0, and the pretreatment process is completed;

[0053] (5) Cobalt electrowinning: Add caustic soda to the vanadium-removed solution to adjust the pH to 3.0, add boric acid to obtain a cathode solution, and electrowinning the cathode solution. When electrowinning cobalt, the cathode is a cobalt starting plate, the anode is a titanium-plated iridium-tantalum plate, and there is no diaphragm electrowinning. Boric acid is added at a dosage of 10 g / L. When electrowinning cobalt, the electrolytic cell temperature is controlled at 60°C and the current density is 200 A / m 2 , the same polar moment is 15cm, and high-purity metallic cobalt is obtained, with a purity of 99.95%. The current efficiency of the electrolytic process is 85.62%. The surface of the electrolytic cobalt obtained is flat. The electrolytic time is 5 days, and no cobalt plate stratification occurs;

[0054] (6) Resin desorption and regeneration: First, wash the resin with pure water, then desorb and regenerate the vanadium-loaded resin. During desorption, use ammonia water with a mass concentration of 2% to flow through the vanadium-loaded resin, control the desorption temperature to 30°C, and the desorbent flow rate to 3BV / h. During regeneration, use sulfuric acid solution with a mass concentration of 5%, and control the flow rate of the sulfuric acid solution to 5BV / h. The regenerated D402 resin can be returned to step (4) for use.

[0055] Example 3

[0056] A method for producing high-purity metallic cobalt from spent hydrogenation catalyst comprises the following steps:

[0057] (1) Calcination-water leaching: The spent hydrogenation catalyst (nickel 40.43%, cobalt 18.90%, vanadium 1.42%) was calcined with sodium carbonate and sodium hydroxide under aerobic conditions. The calcination conditions were as follows: the amount of sodium hydroxide was 1.2 times the theoretical amount of sodium hydroxide used for reaction with vanadium and alumina, and the amount of sodium carbonate was 45% of the amount of sodium hydroxide. The calcination method was staged calcination: in the first stage, the temperature was kept at 400°C for 1 hour, and in the second stage, the temperature was kept at 600°C. The calcined material was kept warm for 3 hours; after the calcination, it was naturally cooled, and there was no obvious agglomeration phenomenon in the calcined material. The calcined material was leached with water at a solid content concentration of 30wt.%, the leaching temperature was 95°C, and the time was 1h, and the solid-liquid separation was performed to obtain a vanadium-containing leaching solution and a water-leached slag; the distribution of nickel and cobalt in the vanadium-containing leaching solution was less than 0.1%, the distribution of vanadium in the vanadium-containing leaching solution was 90%, and the distribution of vanadium in the water-leached slag was 10%; the calcination-water leaching process preliminarily achieved the separation of vanadium and nickel and cobalt in the spent hydrogenation catalyst;

[0058] (2) Acid leaching: The water leaching residue is slurried with water according to a liquid-solid mass ratio of 5:1, and sulfuric acid with a mass concentration of 98% is added for acid dissolution. The pH value of the acid dissolution process is controlled to be 1.5, the acid dissolution time is 1 hour, the temperature is 95°C, and the solid-liquid separation is performed to obtain a nickel-cobalt solution and an acid leaching residue. During the acid dissolution, the nickel-cobalt leaching rate is more than 99%, and the vanadium leaching rate in the acid leaching residue is 75.99% (based on the raw material waste hydrogenation catalyst, the vanadium distribution in the water leaching solution is 90%, the vanadium distribution in the acid leaching residue is 2.40%, and the vanadium distribution in the nickel-cobalt solution is 7.60%).

[0059] (3) Extraction: the nickel-cobalt solution is mixed with P204 to extract impurities, and the P204 raffinate is mixed with Cyanex272 to extract cobalt, to obtain a raffinate A and a loaded organic phase A; 1.5N sulfuric acid solution is added to the loaded organic phase A to wash nickel, and the pH of the washing solution is controlled to be 4.0 to obtain a nickel-containing washing solution and an organic phase A after nickel washing; the organic phase A after nickel washing is mixed with a 3N sulfuric acid solution to strip cobalt, and the pH of the stripping solution is controlled to be 2.5, and the cobalt concentration of the stripping solution is 110 g / L, to obtain a vanadium removal pre-liquid and an organic phase A after stripping;

[0060] P204 mixed extraction impurity conditions: P204 volume concentration 10%, before extraction, P204 sodium saponification with liquid alkali, saponification rate 60%, after sodium soaping, nickel sulfate solution (nickel concentration 30g / L) nickel soaping, saponification temperature 35℃, time 15min, phase ratio 1:1, so as to remove the sodium ions introduced by sodium soap, impurity extraction temperature 35℃, single-stage extraction time 15min, phase ratio 1:1, extraction method is countercurrent extraction 5 levels;

[0061] The conditions for the mixed extraction of cobalt with Cyanex272 are as follows: the volume concentration of Cyanex272 is 15%. Before extraction, sodium Cyanex272 is saponified with liquid alkali, with a saponification rate of 50%. The temperature during saponification is controlled at 35°C, the time is 15 minutes, and the phase ratio is 1:1. When extracting cobalt, the temperature is controlled at 35°C, the single-stage extraction time is 15 minutes, the phase ratio is 1:1, and the extraction method is 5-stage countercurrent extraction.

[0062] (4) Vanadium removal: hydrochloric acid was added to the pre-vanadium removal solution (vanadium concentration 0.35 g / L) to adjust the pH to 1.5, and then the solution was passed through the pretreated D402 resin for dynamic adsorption of vanadium to obtain a post-vanadium removal solution (vanadium concentration 0.2 mg / L). The adsorption temperature was 40°C and the flow rate of the pre-vanadium removal solution was 3 BV / h.

[0063] D402 resin pretreatment: Dynamically wash with 8% sulfuric acid solution at a flow rate of 4BV / h, and then wash the residual acid with pure water at a flow rate of 4BV / h. Stop washing when the pH of the washing water outlet is 3.6, and the pretreatment process is completed;

[0064] (5) Cobalt electrowinning: Since the pH of the solution after vanadium removal is 1.5, which is already between 1.5 and 4.0, there is no need to add liquid alkali to adjust the pH. Boric acid is added to the solution after vanadium removal to obtain a cathode solution, which is then electrowinning. When electrowinning cobalt, the cathode is a cobalt starting plate, the anode is a titanium-plated iridium-tantalum plate, and there is no diaphragm electrowinning. Boric acid is added at a dosage of 6 g / L. When electrowinning cobalt, the electrolytic cell temperature is controlled at 65°C and the current density is 220 A / m 2 , the isopole moment is 12cm, and high-purity metallic cobalt is obtained, with a purity of 99.97%. The current efficiency of the electrolytic process is 87.70%. The surface of the electrolytic cobalt obtained is flat, and the electrolytic time is 5 days without cobalt plate stratification.

[0065] (6) Resin desorption and regeneration: First, wash the resin with pure water, then desorb and regenerate the vanadium-loaded resin. During desorption, use a 5% liquid alkali solution to flow through the vanadium-loaded resin, control the desorption temperature to 40°C, and the desorbent flow rate to 1BV / h. During regeneration, use a sulfuric acid solution with a mass concentration of 8%, and control the sulfuric acid solution flow rate to 4BV / h. The regenerated D402 resin can be returned to step (4) for use.

[0066] Comparative Example 1

[0067] The vanadium removal pre-liquid (vanadium concentration 0.58 g / L) obtained in step (3) of Example 2 was subjected to activated carbon dynamic oil removal and evaporation crystallization. The activated carbon oil removal conditions were as follows: the vanadium removal pre-liquid flow rate was 3 BV / h, the temperature was 35°C, and the discharge density during evaporation crystallization was 1.50 g / cm 3 The obtained cobalt sulfate heptahydrate crystals have no impurities and the cobalt content in the crystalline product is 20.71%, that is, the purity of the cobalt sulfate heptahydrate crystals is 98.71%.

[0068] The cobalt content of the present invention can be detected by conventional methods. The cobalt purity conversion method is to convert the cobalt content into the form of cobalt sulfate heptahydrate crystals. When the purity of cobalt sulfate heptahydrate crystals is 100%, the cobalt content corresponds to 20.98%. Based on this, when the cobalt content is 20.71%, the corresponding purity of cobalt sulfate heptahydrate is 20.71 / 20.98*100%=98.71%.

[0069] Comparative Example 2

[0070] The vanadium-free solution (vanadium concentration: 0.3 mg / L) obtained in step (4) of Example 2 was evaporated and crystallized under the same conditions as in Comparative Example 1, and the obtained cobalt sulfate heptahydrate crystals were free of impurities and had a purity of 98.76%.

[0071] From the data of Comparative Examples 1 and 2, combined with Example 2, it can be seen that within a certain vanadium concentration range, the vanadium concentration has little effect on the appearance quality and purity of the cobalt sulfate heptahydrate crystal product, and there is no problem of poor product appearance quality during crystallization (for example, there is variegated color in the product). The cobalt sulfate heptahydrate on the market is mainly used for battery production, and a cobalt content of more than 20.5% can meet the requirements. Since vanadium does not crystallize together with nickel and cobalt during the evaporation crystallization process, it does not affect the purity of the crystal product.

[0072] The requirements for high-purity electrolytic cobalt are different. First, the cobalt purity is required to be higher, and the application field of high-purity metal cobalt is wider. Secondly, the crystallization and electrolytic deposition behavior of vanadium in the cobalt-containing solution are obviously different, so the removal depth of vanadium in the cobalt-containing solution must be different. The high-purity cobalt sulfate crystals obtained only by crystallization cannot reach a wider range of applications in terms of product and purity. After removing vanadium by the method of Example 2, the purity of the obtained metal cobalt is as high as 99.95%, and the appearance quality is high, that is, the surface of the obtained electrolytic cobalt is flat, the electrolytic deposition time is 5 days, and no cobalt plate stratification occurs.

[0073] Comparative Example 3

[0074] The vanadium removal pre-liquid (vanadium concentration 0.58 g / L) obtained in step (3) of Example 2 was electrolyzed under the same conditions as in Example 2. The surface of the electrolytic cobalt obtained was uneven, and cobalt plate stratification occurred within 24 hours of electrolysis. The cobalt purity was only 98.02%, and the current efficiency was only 76.19%.

[0075] Comparative Example 3 shows that when a cobalt-containing solution without vanadium removal is used to produce metallic cobalt through electrolysis, there are phenomena such as poor product appearance quality, cobalt plate stratification during the electrolysis process, low current efficiency, and lower product purity.

[0076] Comparative Example 4

[0077] The vanadium removal pre-liquid (vanadium concentration 0.58 g / L) obtained in step (3) of Example 2 was subjected to vanadium adsorption by D402 resin. The flow rate of the vanadium removal pre-liquid during adsorption was 6 BV / h, and the other vanadium removal conditions were the same as those in Example 2. The vanadium concentration of the obtained vanadium removal post-liquid was 0.0053 g / L, and the vanadium removal was not thorough. The vanadium removal post-liquid was then subjected to electrolysis under the same conditions as in Example 2. The surface of the obtained electrolytic cobalt was uneven, and cobalt plate stratification occurred within 24 hours of electrolysis. The cobalt purity was only 98.18%, and the current efficiency was only 78.55%.

[0078] Comparative Example 4 shows that when the flow rate of D402 resin adsorption to remove vanadium is too fast or the depth of vanadium removal is not enough, it can also lead to problems such as poor product appearance quality during electrolytic production of metallic cobalt. Compared with Comparative Examples 1 and 2, it can be seen that there are very large differences in the mechanism of the influence of vanadium on product quality during evaporation crystallization and electrolytic deposition.

[0079] Comparative Example 5

[0080] The vanadium-removed liquid (vanadium concentration: 0.0053 g / L) obtained in Comparative Example 4 was evaporated and crystallized under the same conditions as in Comparative Example 1, and the obtained cobalt sulfate heptahydrate crystals had no impurities and the purity of the crystalline product was 98.76%.

[0081] Comparative Example 4 is compared with Comparative Example 5. Both have a vanadium concentration of 0.0053 g / L. However, there is no appearance quality problem when used for evaporation and crystallization. However, when used for electrolytic production of metallic cobalt, it fails to meet the requirements of high-purity metallic cobalt products. In addition, there are a series of problems such as poor product appearance quality.

[0082] In summary, it can be seen from Comparative Examples 1-5 and Example 2 that when the vanadium-containing cobalt salt solution is subjected to extraction of impurities, extraction and separation of nickel and cobalt, and then evaporated and crystallized to produce cobalt sulfate heptahydrate crystals, a small amount of vanadium is not crystallized together with nickel and cobalt during the evaporation and crystallization process, and does not affect the purity and appearance quality of the crystallized product. Therefore, the removal depth of vanadium is relatively low when producing cobalt sulfate crystal products. However, in the production process of electrolytic cobalt products, the removal depth of vanadium has a greater impact on the final product, especially the presence of trace vanadium in the process of electrolytic production of high-purity metallic cobalt will affect the purity of metallic cobalt, and vanadium has a variety of valence states in the aqueous solution, and its existence form is easy to change, which leads to the current efficiency being very easy to reduce during electrolytic deposition. When vanadium and cobalt cobalt coexist, the electrolytic behavior of vanadium will lead to uneven deposition of cobalt metal, produce cobalt plate stratification phenomenon, and the final product has poor appearance quality, and will also lead to a reduction in the purity of metallic cobalt. Therefore, when using waste hydrogenation catalyst to recover and prepare high-purity metallic cobalt, the depth separation of cobalt and vanadium is the key to the purity, appearance quality and current efficiency of the electrolytic cobalt that affects metallic cobalt. It can be seen that the synergistic effect of the various steps of the present invention can produce metallic cobalt with high quality and high purity.

[0083] The above description is a detailed description of the preferred feasible embodiments of the present invention, but the embodiments are not intended to limit the scope of the patent application of the present invention. All equivalent changes or modified changes completed under the technical spirit suggested by the present invention should fall within the patent scope covered by the present invention.

Claims

1. A method for producing high-purity metallic cobalt from spent hydrogenation catalysts, characterized in that: The following steps are involved: (1) Calcination and water leaching: the spent hydrogenation catalyst is calcined with sodium carbonate and sodium hydroxide under aerobic conditions, cooled naturally, leached with water, and solid-liquid separated to obtain a vanadium-containing leaching solution and water-leached residue; (2) Acid leaching: Acid leaching is performed on the water leaching residue to extract nickel and cobalt. After the leaching is completed, the solid and liquid are separated to obtain a nickel-cobalt solution and acid leaching residue; (3) Extraction: the nickel-cobalt solution is mixed with P204 to extract impurities, the P204 raffinate is mixed with extractant A to extract cobalt, and the raffinate A and loaded organic phase A are obtained; the loaded organic phase A is mixed with an inorganic acid solution to strip cobalt, and the vanadium removal pre-liquid and the stripped organic phase A are obtained; (4) Vanadium removal: adjusting the pH of the pre-vanadium removal solution to 0-1.5, and then passing it through the pretreated D402 resin to dynamically adsorb vanadium to obtain a post-vanadium removal solution; (5) Cobalt electrowinning: Adjust the pH of the solution after vanadium removal to 1.5-4.0, add boric acid to obtain a cathode solution, and electrowinning the cathode solution to obtain high-purity metallic cobalt.

2. The method for producing high-purity metallic cobalt from spent hydrogenation catalyst according to claim 1, characterized in that: In the step (1), the amount of sodium hydroxide used is 1.2-1.5 times the theoretical amount used for the reaction with vanadium and aluminum oxide, and the amount of sodium carbonate used is 30-60% of the weight of the sodium hydroxide.

3. The method for producing high-purity metallic cobalt from spent hydrogenation catalyst according to claim 1, characterized in that: In the step (1), the roasting method is staged roasting: the first stage is at a temperature of 300-400°C and a time of 1-3 hours; the second stage is at a temperature of 600-1000°C and a time of 1-3 hours.

4. The method for producing high-purity metallic cobalt from spent hydrogenation catalyst according to claim 1, characterized in that: In the step (1), water is added until the solid content is 20-35 wt.%, and the temperature during water immersion is 60-95° C. for 1-4 hours.

5. The method for producing high-purity metallic cobalt from spent hydrogenation catalyst according to claim 1, characterized in that: In the step (2), the pH value of the acid dissolution process is controlled to be 0.5-1.5, the acid dissolution time is 1-4 hours, and the temperature is 60-95°C.

6. The method for producing high-purity metallic cobalt from spent hydrogenation catalyst according to claim 1, characterized in that: In the step (3), the ratio of P204 to impurities is controlled at 1-2:1, the extractant A is P507 or Cyanex272, and the ratio of cobalt to cobalt is controlled at 1-1.5:

1.

7. The method for producing high-purity metallic cobalt from spent hydrogenation catalyst according to claim 1, characterized in that: In the step (3), before stripping cobalt, the loaded organic phase A is firstly washed with nickel. When stripping cobalt with the loaded organic phase A, the cobalt concentration of the stripping solution is controlled to be 80-110 g / L.

8. The method for producing high-purity metallic cobalt from spent hydrogenation catalyst according to claim 1, characterized in that: In the step (4), the pretreatment of the D402 resin is specifically as follows: a mineral acid solution with a mass concentration of 5-10% is used for dynamic washing at a flow rate of 3-5BV / h, and then the residual acid is washed with pure water at a flow rate of 3-5BV / h. The washing is stopped when the pH value at the washing water outlet is 3-4, and the pretreatment is completed. In the step (4), when the D402 resin adsorbs vanadium, the adsorption temperature is controlled to be 20-40°C, and the flow rate of the liquid before vanadium removal is 2-5BV / h.

9. The method for producing high-purity metallic cobalt from spent hydrogenation catalyst according to claim 1, characterized in that: In the step (5), boric acid is added in an amount of 6-15 g / L, and the control conditions during the electrolytic deposition of cobalt are: the electrolytic cell temperature is 55-65° C., the current density is 180-220 A / m 2 , isopole moment 10-15cm.

10. The method for producing high-purity metallic cobalt from spent hydrogenation catalyst according to claim 1, characterized in that: In the step (5), during the cobalt electrowinning, the cathode is a cobalt starting plate, the anode is a titanium-iridium-tantalum plate, and there is no diaphragm electrowinning.

Citation Information

Patent Citations

  • Multi-element recycling of residual oil hydrogenation waste catalyst

    CN113293297A

  • Method for recovering vanadium in waste hydrogenation catalyst

    CN118308607A

  • Method for extracting valuable metals from acid leaching solution of nickel-molybdenum multi-metal metallurgical materials by separation

    CN101838735A

  • Process for purifying cobalt by electro-depositing cobalt chloride solution through cyclone electrolysis technology and reclaiming residual chlorine

    CN102808194A

  • Method for producing metal cobalt by sulfuric acid system electrodeposition

    CN111826525A